PENYIMPANAN BAHAN MAKANAN DI BEI CAFE BANDUNG - Antonius Iskandar Yahya; Raden Intan Medya Ratna Puri; Jonathan Raffaelo (Bajang Institute, 2025)
This study aims to identify and analyze the level of food ingredient storage at Bei Cafe Bandung. The research was conducted at Bei Cafe Bandung with a population of 7 kitchen staff members. The research method used is a descriptive analytical method employing continuum analysis. The results of the study are as follows: 1)The level of appropriate storage location at Bei Cafe Bandung falls into the good category, with an average score of 148.00; 2)The level of appropriate storage timing is in the fair category, with an average score of 116.00; 3)The level of appropriate storage quality is also in the fair category, with an average score of 112.00; 4)The level of appropriate storage quantity falls into the fair category, with an average score of 77.00; 5)The level of appropriate storage value is in the good category, with a score of 74.00. The overall analysis results indicate: 1)Appropriate location is in the good category; 2)Appropriate timing is in the fair category; 3)Appropriate quality is in the fair category; 4)Appropriate quantity is in the fair category; 5)Appropriate value is in the good category. The conclusion of this study is that food ingredient storage at Bei Cafe Bandung is not yet optimal.